Advanced governing for capital flight - Amedzro St-Hilaire, Walter (Burlington, ON, Canada ; Palm Bay, Florida, USA : Apple Academic Press, 2020)
c
The Dimensions and Flaws of Tax Evasion -- A Finance Greatly Marked by Offshore -- The Limits of International Financial Statistics on Offshore Practices -- The Role of Bleaching Mechanisms -- Diversification of Countermeasures and Strengthening Them -- Worrying Business for Banks' Reputations -- An Opportunistic Nonfinancial Sector and Deterritorialized Financial Entities -- Countermeasures to be Confirmed in the Face of Tax Optimization -- The Taxation of the Financial Sector, An Opacity to Overcome -- What is the Real Tax Contribution Rate of Banks? -- The Proven Role of Intermediaries in Tax Evasion -- Regulation of Intermediaries Does Not Prevent Massive Tax Evasion -- Focus on Intelligence and Action Against Clandestine Financial Circuits -- A Timid Shift in the Mindset Sets and Practices of Intermediaries -- Learn More About the Mechanisms to Better Combat Capital Evasion -- Strengthening the Powers and Involvement of the Judiciary in the Fight Against Capital Evasion.
OCLC-licensed vendor bibliographic record.
Keywords: Tax evasion; Capital movements; Capital flight tax; BUSINESS & ECONOMICS / Business Law; BUSINESS & ECONOMICS / Corporate Finance; BUSINESS & ECONOMICS / Finance